PORTFOLIO DIVERSIFICATION OPPORTUNITIES FOR NIGERIA’S ISLAMIC (SHARIAH) STOCK INVESTORS WITH THEIR MAJOR TRADING PARTNERS - Abdulkarim, Fatima Muhammad; Ali, Hamisu Sadi; Muye, Ibrahim Muhammad; Tabash, Mosab I. (Journal of Islamic Monetary Economics and Finance, 2025)
This paper investigates potential diversification opportunities for Nigeria’s Islamic stock investors with Nigeria’s top trading partners (France, Spain, United Kingdom and India). It employs daily data of Islamic stock indices, namely Nigeria’s LOTUS Islamic index and FTSE shariah indices of the four countries, from 14 July 2015 to 14 December 2022. Using multivariate GARCH-DCC, we show that Islamic investors from Nigeria have almost no portfolio diversification opportunities in the Islamic stock markets of these countries except for a slight portfolio diversification opportunity found in the UK Islamic stock market for a very short period (one year) and almost none for India, Spain, France. The results from the continuous wavelet transform (CWT) however suggest that diversification opportunities are present in UK, France, Spain and not in India. These findings have important policy implications for policy makers and investors seeking to invest in these countries to be mindful of the appropriate investment timing to minimize potential future losses in investments.